Impact of the COVID-19 Pandemic on Psychiatric Admissions to a Large Swiss Emergency Department: An Observational Study - Ambrosetti, Julia; Macheret, Laura; Folliet, Aline; Wullschleger, Alexandre; Amerio, Andrea; Aguglia, Andrea; Serafini, Gianluca; Prada, Paco; Kaiser, Stefan; Bondolfi, Guido; Sarasin, François; Costanza, Alessandra (International journal of environmental research and public health, 2021)
The coronavirus disease 2019 (COVID-19) pandemic is a public health emergency with profound mental health consequences. The psychiatric emergency department (ED) plays a key role during this mental health crisis. This study aimed to investigate differences in admissions at a Swiss psychiatric ED from 1 April to 15 May during a “pandemic-free” period in 2016 and a “during-pandemic” period in 2020. The study included 579 consultations at psychiatric ED in the “during-pandemic” period and 702 in the “pandemic-free” period. Sociodemographic and clinical characteristics were compared, and logistic regression analysis was performed to identify variables associated with psychiatric admissions during the pandemic. A reduction in total psychiatric ED admissions was documented during COVID-19. Logistic regression analysis predicted the independent variable (ED admission during the pandemic) and estimated odds ratio (OR) for being unmarried/not in a relationship, arrival in an ambulance, suicidal behavior, behavioral disorders and psychomotor agitation. Though only statistically significant in bivariate analysis, patients were also more likely to be involuntarily hospitalized. This picture appears to be reversed from a sociodemographic and clinical point of view to our observation of psychiatric ED consultation in 2016. These findings highlight that the reduction in psychiatric ED admissions during the pandemic seems to be associated with living alone and more severe psychopathologies, which must alert psychiatrists to ensure access to mental health care in times of pandemic.